Increasing Moral Emotions Through Traditional Games of Gobak sodor and Bentengan Using the Experiential Learning Method - Iswinarti Iswinarti; Wahyu Nur Laily (Indigenous: Jurnal Ilmiah Psikologi, 2024)
The decline in morality has been of interest in the education world, especially among junior high school students. They tend to justify their mindset and actions when making decisions about problem-solving. Moral emotion is an essential aspect to have before any decision-making. Students must have moral emotions to avoid repeating mistakes and bad behavior. Efforts to increase moral emotions through the traditional game "Gobak Sodor and Bentengan". This research aims to determine whether the traditional games of gobag sodor and bentengan can be a model for increasing moral emotions in students. This research is a quasi-experimental research with a pretest-posttest control group design. The number of subjects was 30 junior high school students aged 12-15 years. The sampling technique used was purposive sampling. The results of the Wilcoxon test research showed that there were significant differences in experimental group 1 (0.009; 0.006; 0.022 < 0.05) and experimental 2 (0.014; 0.006; 0.006 < 0.05) between the pretest and post-test. The Mann-Whitney results showed significant differences between the experimental and control groups (p < 0.05).